Effect of cerium oxide on erythrocyte deformability in rat lower extremity ischemia reperfusion injury - Tatar, T; Polat, Y; Comu, F M; Kartal, H; Arslan, M; Kucuk, A (Bratislavské lékarské listy, 2018)
Cerium oxide is the oxide form of cerium, which has protective effects in ischemia reperfusion (I/R) injury. The purpose of our study was to look into the effects of this rare-earth metal on erythrocyte deformability in rat lower extremity I/R injury model. We used 24 Wistar albino rats as subjects in our study. They were divided into 4 groups; randomized control group (group C; n = 6), cerium oxide group 0.5 mg.kg-1, intraperitoneal (group CO; n = 6), I/R group (group I/R; n = 6) and I/R group with cerium oxide 0.5 mg.kg-1 intraperitoneally (group I/R-CO; n = 6). Erythrocyte packs were prepared from heparinized blood samples and deformability measurements were performed. We obtained similar results from the control and I/R-CO groups (p = 0.158). The results in I/R group were evidently higher than those of the control, CO, and IR-CO groups (p < 0.0001, p < 0.0001, p = 0.001, respectively). We detected unfavorable effects of I/R on erythrocyte deformability, which may impair blood flow and hence tissue perfusion in infrarenal rat aorta. We also found that cerium oxide had beneficial effects by reversing undesirable effects of I/R. Further studies with larger volume are required to support our promising results (Fig. 1, Ref. 24).